Global engagement and innovation activities: The case of Malaysian manufacturing firms - Lim Ee Shiang; Cassey Lee (Asian Development Bank Institute (ADBI), 2022)
This paper aims to examine how the diversity of global engagement is related to firms' participation in innovation input and output activities in the Malaysian manufacturing sector. The study uses firm-level data obtained from the World Bank's Enterprise Survey 2015. Firms are classified into four different groups based on their engagement in global activities, i.e., foreign trade and foreign direct investment. Incidences of innovation for ten innovation activities are computed. The incidence of innovation was used to examine the extent to which different global engagement groups participate in ten various types of innovation activities. Logit models are used to estimate the probability of engaging in innovation input and output activities for firms with differing global engagements. Generally, the results clearly highlight that globalized firms, i.e., firms engaging in global activities, participate in innovation activity more actively than their nonglobalized counterparts, despite there being some evidence that the pattern of engagement in innovation activity varies across globalized firms. Empirical findings propose that trade policies promoting exporting and policies attracting foreign direct investment may be useful in driving firms' participation in innovation activity. A number of export-related policies can be formulated to assist domestic firms in integrating into the global value chain. These include providing easier access to information about foreign markets, export marketing development assistance, and training programs. In addition, foreign direct investment liberalization policies may be used to attract selective foreign direct investments, and tax-related incentive policies may be formulated to encourage firms to set up in-house R&D activities for product development.
Keywords: F61; L60; O31; 330; exports; foreign ownership; global engagement; innovation; R&D